Ibm Aplikasi Kelompok Nelayan Transplantasi Karang Untuk Meningkatkan Produksi Perikanan - Suci Puspita Sari; Sudirman Adibrata; Dwi Rosalina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2015)
Coral transplantation technology is a rehabilitation effort through grafting or cutting live corals to be planted in other places that are damaged. Transplantation can accelerate the regeneration of damaged coral reefs and to build areas that previously did not have coral reefs. Transplantation activities are carried out in the waters of Camban Bay, using a relatively easy method and a high level of efficiency so that it is more effective in the process of making and applying it. This activity uses iron skeleton media. The iron frame is used as a place to attach the fragments to be transplanted. Coral transplantation in Camban Bay produces outcomes in the form of fish and coral reefs. Monitoring of coral transplantation showed good growth of coral fragments. The growth of coral fragments per month is ± 0.6 cm and with a survival rate of 35%.